If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24=4(x+5)-2x
We move all terms to the left:
24-(4(x+5)-2x)=0
We calculate terms in parentheses: -(4(x+5)-2x), so:We get rid of parentheses
4(x+5)-2x
We add all the numbers together, and all the variables
-2x+4(x+5)
We multiply parentheses
-2x+4x+20
We add all the numbers together, and all the variables
2x+20
Back to the equation:
-(2x+20)
-2x-20+24=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2
| (X-1)(x+1)+5x-3=0 | | x^2/x+14=11 | | 3+6x8+9=153 | | 2t-10=0 | | (0.5x^-1/2)-(16x^-3)=0 | | -3+-3x+x3=0 | | 25.6x=15x+123.45 | | x=2√x+3 | | 4x−3 2−5−2x 3−3x−4 3=5 | | 6/15=x/10 | | 1-2x=-x-5 | | 2z/9+7=-2 | | x/10+5=-7 | | z/8+1=10 | | 25y+2=-7 | | 32=3x-4 | | t÷4-1=9 | | a÷5+1=9 | | (7)=5^{2x-9}=3125$ | | x+3x=3344 | | 2x-5=3x-11 | | 2x²-11x-21=0 | | 2.4x+1.35-0.04x=3.71x×10.8 | | 2/3(3x-4)+3x=5/6 | | (2x)^2+(3x)^2=26^2 | | 9x+3=10x-15 | | -8x+9=2x-7 | | 17-9=y+5 | | 254(2x5)=-61 | | 2=m/ | | 4(x-4)+5(8-x)=7x-(6+2x) | | 3×+2y=11 |